2014
DOI: 10.11648/j.jfns.20140203.15
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Nutritional, Phytochemical and Microbiological Quality of Three Pepper Varieties

Abstract: Abstract:The study investigated the comparative evaluation of nutritional, phytochemical, and microbiological quality of three pepper varieties (Capsicum annuum, Capsicum genus, and Capsicum frutescens). Three pepper varieties were purchased fresh from local market in Calabar, Cross River State. The samples were washed with distilled water and thinly sliced, (diameter of 1.0±0.1cm and thickness of 3-4mm), and then treated with chlorine concentrated solution. These samples were oven dried at temperature of 60 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 9 publications
5
28
0
Order By: Relevance
“…Although numerous studies of metabolite composition in pepper fruits have reported, they have mainly focused on determining the concentrations of carotenoids, capsaicinoids, vitamins, and phenolic compounds. In contrast, information is limited for other nutritional compositions such as proximates, minerals, amino acids, and fatty acid profiles in pepper varieties [20]. Furthermore, few studies about genotypic and environmental effects on those compounds in pepper fruits are available.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies of metabolite composition in pepper fruits have reported, they have mainly focused on determining the concentrations of carotenoids, capsaicinoids, vitamins, and phenolic compounds. In contrast, information is limited for other nutritional compositions such as proximates, minerals, amino acids, and fatty acid profiles in pepper varieties [20]. Furthermore, few studies about genotypic and environmental effects on those compounds in pepper fruits are available.…”
Section: Introductionmentioning
confidence: 99%
“…Emmanuel-Ikpeme et al (2014), reported that Capsicum genus had the highest moisture content of 11.16% followed by Capsicum frutescens with a value of 10.14% while Capsicum annuum had the least value of 9.43%. The high level of moisture in all the samples investigated revealed that the flour had high water activity which could enhance microbial action bringing about food spoilage as reported by Emmanuel-Ikpeme et al (2014). Therefore, long storage should be discouraged except further drying is employed.…”
Section: Chemical Composition Of Wheat Flour Spiced With Chili Peppermentioning
confidence: 67%
“…The fine powdered pungent product is a necessary flavoring and coloring ingredient in the common traditional sauce 'Wot' while mature green pods ('karia') are eaten as salads (Shumeta, 2012). Moreover, hot pepper is rich source of soluble and insoluble fibers, vitamins (C, niacin, A, E, K and folic acid) and minerals (calcium, sodium, magnesium, phosphorus and copper) (Grubben & Denton, 2004;Emmanuel-Ikpeme, Henry, & Okiri, 2014). Ethiopians believe that a person who frequently consumes hot pepper has resistance to various diseases (Shumeta, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ethiopians believe that a person who frequently consumes hot pepper has resistance to various diseases (Shumeta, 2012). This is attributed to the chemical composition of hot pepper fruit in that it contains higher amount of tannins, flavonoid, saponin, terpenoid and carotenoids as compared to other species of capsicum (Emmanuel-Ikpeme et al, 2014). Besides, capsaicin has shown anti-oxidant, antimutagenic, anticarcinogenic and immunosuppressive activities.…”
Section: Introductionmentioning
confidence: 99%